Motion sensors based sports training buddy - Chua, Darren Qi Yang (Nanyang Technological University, 2020)
Engaging in muscle strengthening activities at least twice per week is strongly encouraged by World Health Organization (WHO) due to the potential health benefits. However, not all users of weight training are well equipped with the right exercise techniques for those exercises, due to lack of knowledge. Hence, without guidance from qualified professional trainers, there is a possibility of users injuring themselves as they are not using the equipment correctly. This paper aims to meet the following objectives: (1) To understand the current fitness trends and existing fitness trackers/devices along with their functions and shortfalls; (2) To understand the weight training exercises and their exercise risk; (3) To design and implement a training buddy system through a user-interface (software) utilizing a motion sensor (hardware) to track sensor tag’s movement in 3D space and correct user’s exercise techniques; (4) To utilize data collected from user to provide live feedbacks to the users during exercise to correct posture error; (5) To propose new solutions and recommendation that will be integrated into the training buddy system “Trainex” to help users create better posture awareness. The design and implementation of this system comprises of both hardware and software. The hardware consists of motion sensors and microprocessors where data was collected and processed before sending real time data via Bluetooth Low Energy. The software uses Arduino and Android application to program the microprocessor and create a platform to feedback the user about their exercise techniques. This system provides real time updates to the users during exercise, providing feedbacks on their exercise posture, thus helping the users to rectify their incorrect posture immediately during every repetition. This training buddy system “Trainex” seeks to benefit both recreational and competitive gym-goers or athletes targeted at specialized weight training exercises (i.e. Deadlift, Squat, Bench Press), at an affordable yet cost-effective pricing. Thus, achieving its aim to help minimize exercise injuries and risk, creating a safe environment for everyone to train in without the aid of a qualified professional trainers.